Interferência do diabetes mellitus tipo I nos níveis de lactose na transição entre as fases I e II da lactogênese em mulheres puérperas - Oliveira, Angela Maria de Morais (2005)
Lactogenesis is constituted by two phases, called as lactogenesis I and lactogenesis II. The transition between those phases is characterized by increase in the lactose concentration. This study aimed to evaluate the interference of diabetes mellitus in the lactose concentration associated to transition between phases I and II of lactogenesis. It was studied 11 puerperal women with pre-gestational diabetes mellitus and 19 without diabetes. During the five first days after delivery, at each 24 hours, it was collected colostrums samples to evaluate its lactose concentration by reaction with picric acid. In both groups there were progressive increases in the lactose levels with time. The lactose concentrations in both groups exhibited statistically significant sigmoidal dependences with the time after delivery, with neat two-state transition between the phases I and II of lactogenesis. The analysis of those transitions revealed an 18 hours time delay in the beginning of lactogenesis II of diabetes carriers women with inadequate metabolic control in relation to puerperal females without diabetes.